Gambaran Penyesuaian Sosial pada Remaja Low Vision di Sekolah Inklusi Kota Padang - Kurniati Ramadhini; Annisa Kharisma; Andika Bayu Putra; Sry Apfani; Rahmia Tulljanah (Jurnal Syntax Admiration, 2024)
Adolescents will face developmental tasks that must be completed before entering the next stage of development. One of them is to build stronger social relationships with peers, both with the same sex and the opposite sex. Adolescents need social adjustment to adapt to new tasks. The purpose of this study is to find out about social adjustments made by adolescents who have vision problems at the Padang City Inclusion School. This research was conducted in a qualitative descriptive way. The three teenagers who experienced low vision impairment were junior high and high school students at the Padang City Inclusion School. They are the informants of this research. The purposive sampling method is used to select informants. Interviews and observations were used to collect data. The results showed that the three informants had good social adjustment while studying at an inclusion school. They use their abilities to participate in social activities, utilize the rest of their vision, provide assistance, be willing to cooperate, accept dissent, seek to forgive others, and obey the rules.